A comprehensive exploration on the development of nano Y2O3 dispersed in AA 7017 by mechanical alloying and hot-pressing technique. Issue 16 (15th August 2021) - Prashanth, M.; Karunanithi, R.; RasoolMohideen, S.; Sivasankaran, S.
Abstract: The main objective of the present study is to develop AA 7017 alloy matrix reinforced with yttrium oxide (Y2 O3, rare earth element) nanocomposites by mechanical alloying (MA) and hot pressing (HP) techniques for armor applications. AA 7017+10 vol % Y2 O3 nanocomposites were synthesized in a high-energy ball mill with different milling times (0, 5, 10, and 20 h) to explore the structural refinement effect. The phase analysis and homogeneous dispersion of Y2 O3 in AA 7017 nanocrystallite matrix were investigated by X-ray diffraction (XRD), various electron microscopes (HRSEM, and HRTEM), Particle Size Analyzer (PSA), and Differential Thermal Analysis (DTA). The nanostructured powders were hot-pressed at 500 MPa pressure with a temperature of 673k for 1hr. The consolidated sample results revealed significant grain refinement and the enhanced mechanical properties with the function of milling time in which the 20h sample exhibited improvement in the hardness (142 VHN - 260 VHN) and ultimate compressive strength (514 MPa–906.45 MPa) due to effective dispersion of Y2 O3 . The various strengthening mechanisms namely, grain boundary (27.02–32.69 MPa), solid solution (57.21 MPa), precipitate (189.79–374.62 MPa), Orowan (135.68–206.92 MPa), and dislocation strengthening (84.99–149.82 MPa) were determined and correlated to the total strength.